Testing of the Nursing Evidence‐Based Practice Survey. Issue 2 (31st March 2020) - Crawford, Cecelia L.; Rondinelli, June; Zuniga, Stephen; Valdez, Regina M.; Cullen, Laura; Hanrahan, Kirsten; Titler, Marita G.
Abstract: Background: Clinicians' knowledge and skills for evidence‐based practice (EBP) and organizational climate are important for science‐based care. There is scant literature regarding aligning organizational culture with EBP implementation and even less for unit and organizational culture. The Nursing EBP Survey examines individual, unit, and organizational factors to better understand registered nurses' (RN) self‐reported EBP. Aims: Establish and confirm factor loading, reliability, and discriminant validity for the untested Nursing EBP Survey. Methods: The study employed a descriptive cross‐sectional survey design and was targeted for RNs. The setting included 14 hospitals and 680 medical offices in Southern California. The 1999 instrument consisted of 22 items; 7 items were added in 2005 for 29 items. The questionnaire used a 5 point, Likert‐type scale. The survey website opened in November 2016 and closed after 23 weeks. Psychometric testing and factor determination used parallel analysis, exploratory factor analysis, confirmatory factor analysis (CFA), and ANOVA post hoc comparisons. Results: One thousand one hundred and eighty‐one RNs completed the survey. All factor loadings in the CFA model were positive and significant ( p < .001). All standardized loadings ranged from .70 to .94. The covariance estimate between Factor 1 and Factor 2 was marginally significant ( p = .07). All other covariances and error variances were significant ( p < .001). Final factor names were Practice Climate (Factor 1), Data Collection (Factor 2), Evidence Appraisal (Factor 3), Implementation (Factor 4), and Access to Evidence (Factor 5). Four of 5 factors showed significant differences between education levels ( p < .05 level). All factors showed significant differences ( p < .05) between inpatient and ambulatory staff, with higher scores for inpatient settings. Linking Evidence to Action: Nurses' knowledge, attitudes, and skills for EBP vary. The 2019 Nursing EBP survey offers RNs direction to plan and support improvement in evidence‐based outcomes and tailors future EBP initiatives.